Alkali resistance testing methodology and development: Focus on mullite based castables. Issue 4 (28th April 2022) - Haines, Katherine; Byrd, Kasandralee; Lankard, David
Abstract: Aluminosilicate refractories, which are widely used in alkali‐rich environments, typically have a matrix that is close to mullite in composition. It is the matrix component that is most vulnerable to attack in service. In this study, the "matrix" is identified as including the mixed water and the solid constituents with a particle size less than 0.5 mm. The formulation of experimental compositions was done on a volume percent basis to account for differences in the specific gravity of the components. This approach fixes the volume percent of water and provides the means to replace any of the solid constituents with an equal volume of other refractory materials. Aided by using polished thin sections, characterization procedures provide for the generation of information on microstructural, chemical, and mineralogical changes of the matrix after exposure to a corrosive environment. Abstract : Aluminosilicate refractories are characteriazed for microstructural, chemical, and mineralogical changes after exposure to a corrosive environment. Pictured are post‐test thin sections viewed at 200x magnification with crosspolarizing light. The reaction product and elongated phases found at the reaction interface are shown.